Edge localized mode control using n = 1 resonant magnetic perturbation in the EAST tokamak. (12th December 2016) - Sun, Y.; Jia, M.; Zang, Q.; Wang, L.; Liang, Y.; Liu, Y.Q.; Yang, X.; Guo, W.; Gu, S.; Li, Y.; Lyu, B.; Zhao, H.; et al.
Abstract: A set of in-vessel resonant magnetic perturbation (RMP) coil has been recently installed in EAST. It can generate a range of spectrum, and there is a relatively large window for edge localized mode (ELM) control according to the vacuum field modeling of the edge magnetic island overlapping area. Observation of mitigation and suppression of ELM in slow rotating plasmas during the application of an n = 1 RMP is presented in this paper. Strong ELM mitigation effect is observed in neutral beam injection heating plasmas. The ELM frequency increases by a factor of 5, and the crash amplitude and the particle flux are effectively reduced by a similar factor. Clear density pump-out and magnetic braking effects are observed during the application of RMP. Footprint splitting is observed during ELM mitigation and agrees well with vacuum field modelling. Strong ELM mitigation happens after a second sudden drop of plasma density, which indicates the possible effect due to field penetration of the resonant harmonics near the pedestal top, where the electron perpendicular rotation becomes flat and close to zero after the application of RMP. ELM suppression is achieved in a resonant window during the scan of the n = 1 RMP spectrum in radio-frequency (RF) dominant heating plasmas. The best spectrum for ELM suppression is consistent with the resonant peak of RMP by taking into account of linear magnetohydrodynamics plasma response. There is no mode locking during the application of n = 1 RMP in ELMy H-mode plasmas, although the maximal coil current is applied.